ANTIOXIDANT ACTIVITY OF ETHYL ACETATE EXTRACT OF RED Psidium guajavaL. LEAVES GROWN IN MANOKO, LEMBANG - INDONESIA - Fidrianny, Irda; Hartanti, Rika; Raveendaran, Narmmatha (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2012)
Psidium guajava L. (Myrtaceae) is a well known plant in Malaysia and Indonesia. Its leaves extract was found to possess antidiarrhea, antimicrobial, hepatoprotective and antioxidant activities. Objective of this research is to isolate an antioxidant subtance from Red Psidium guajava L. leaves. The crude leaves was extracted using Soxhlet apparatus by gradual polarity of three different solvents, n-hexane, ethyl acetate and methanol. Antioxidant activity of each extract was tested by using DPPH (2,2-diphenyl-1-picrylhydrazyl) radical scavenging method. Total phenol, total flavonoid and total tannin content of the extracts were also measured. Ethyl acetate extract was fractionated using vacuum liquid chromato-graphy for fractionation. Purification was performed using TLC preparative. Isolate then characterized using specific spray reagent, UV-Vis spectrophotometry and infrared spectrophotometry. Crude drug of Psidiumguajava contained flavonoid, tannin, quinone, saponin and steroid/ triterpenoid. Antioxidant activity of ethyl acetate extract is 65.63% with total phenol 4.25%, total flavonoid 0.53% and total tannin 1.16%. Antioxidant compound N was isolated from ethyl acetate extract.Antioxidant compound N was supposed to be aglycone flavone that has OH at C -4’, C-5 and C-7.Key words: Psidium guajava L. , antioxidant activity, ethyl acetate extract